Evaluation of extracellular vesicles isolated from the cerebrospinal fluid and plasma from former National Football League players at risk for chronic traumatic encephalopathy: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Muraoka, Satoshi; Jedrychowski, Mark P.; Yang, Zijian; Tatebe, Harutsugu; DeLeo, Annina M.; Yukawa, Kayo; Ko, Jina; Wang, Katherine; Ikezu, Seiko; Gygi, Steven; Issadore, David; Tokuda, Takahiko; et al.
Abstract: Background: Chronic Traumatic Encephalopathy (CTE) is a tauopathy that affects individuals with a history of mild repetitive brain injury frequently seen in contact sports. Initial neuropathologic change of CTE consists of perivascular deposition of phosphorylated tau (p‐tau) in cortical neurons. Tau pathology progresses to form neurofibrillary tangles in neurons throughout the brain in later stages when patients show more clinical symptoms. Extracellular vesicles (EV) are known to carry neuropathogenic molecules in neurodegenerative disease and able to cross the blood brain barrier. We therefore examined the protein composition of EV separated from cerebrospinal fluid (CSF) and plasma in former NFL players with cognitive dysfunction, and an age‐matched controls. Method: EVs were separated from CSF and plasma from former NFL players (n=4, 14) and controls (n=5, 12) by affinity separation or size exclusion chromatography, respectively. The EV protein profiling was characterized by SIMOA for tau and p‐tau and mass spectrometry. The protein data was analyzed for EV enrichment, differentially expressed proteins, pathway analysis and correlation with cognitive function, head impact and tau/p‐tau levels by biostatistics and bioinformatics. Result: The level of t‐tau and p‐tau in plasma EVs from former NFL players was significantly elevated although there was no significant change in CSF EV compared to the control. The 95 proteins were commonly identified between the paired plasma‐CSF from the same patients, but there was no significant correlation with the disease status. Collagen alpha‐3(VI) chain (COL6A3), ‐1(VI) chain (COL6A1) and Reelin (RELN) were differentially expressed in former NFL players' plasma EVs. A combination of these 3 proteins in plasma EV was able to distinguish former NFL players from controls with 85% accuracy by machine learning. Conclusion: These data suggest that COL6A3, RELN and COL6A1 in plasma EV can be potential biomarker for monitoring the CTE development. We need further evaluation of CSF EV by increasing the sample number size in future studies.